Clinico-pathologic profile of women with palpable breast lumps in Chitwan Medical College, Nepal - S, Ranabhat; M, Subedi; A, Bhandari; M, Tiwari; S, Maharjan; J, Kshetri; BP, Osti (International Journal of Research in Medical Sciences, 2017)
Background: Spectrum of female breast diseases is manifold and includes various non-neoplastic and neoplastic conditions. This study focused on the clinico-pathological profile of several breast diseases, including fibrocystic change, fibroadenoma and breast carcinoma. Methods: This cross sectional analytic observational study included Fine Needle Aspiration Cytology cases of female breast diseases diagnosed over three years from 2011 to 2014 in Chitwan Medical College Teaching hospital in Central Nepal. Univariate analysis was carried out to find out age group-wise proportion of the diseases in relation to five cytologic categories and various cytomorphologic diagnoses. Independent samples t-test was used to find out the significance of difference between mean age of benign and malignant breast diseases. Results: The proportion of benign, suspicious for malignancy and malignant breast diseases was 90.4 %, 0.8% and 8.8 % respectively. The mean age of patients at diagnosis for benign diseases and malignant disease was 31.7± 10.4 years and 49.2 ± 12.0 years respectively. t-test showed difference in mean age between benign and malignant diseases to be statistically significant (t=8.79, p= <0.001). Fibrocystic change and fibroadenoma were the most common breast disease overall and the most common neoplasm respectively. 58.1 %, 25.9 % and 6.5 % of all carcinoma cases in this study were found below 50, below 40 and below 30 years of age respectively. Conclusions: Fibrocystic change and fibroadenoma are most common disease of breast and most common neoplasm of breast respectively. Breast cancer occurs in younger women in Nepal in comparison to women in developed countries. Therefore, breast cancer prevention programs in Nepal should target young women also.